Method for inhibiting gelatinization of polyanion positive electrode material slurry

Through the compounding technology of polyvinylidene fluoride and non-fluorine binder, combined with the staged mixing of conductive slurry and non-fluorine binder, the problem of easy gelation of polyanionic cathode material slurry is solved, and the slurry is achieved Improved stability and coating quality.

CN119340324APending Publication Date: 2025-01-21BENAN ENERGY TECH JIANGSU CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411467843.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Polyanionic positive electrode materials are prone to gelation during the preparation process, making it difficult to achieve the capacity of the material close to the theoretical capacity, and the high residual alkali amount makes the battery cell slurry easy to gel and gas production during charging and discharging.

Method used

Polyvinylidene fluoride and non-fluorine binder are used for compounding. The conductive slurry and non-fluorine binder are mixed, and the mixed powder is stirred in stages to ensure that the non-fluorine binder can effectively neutralize the polyvinylidene fluoride. Eliminate reactions and inhibit gelation.

Benefits of technology

Effectively slows down the gelation of the polyanionic cathode material slurry, extends the coating window period, improves the coating quality of the cathode sheet, improves the stability of the slurry after gelation, and ensures that the viscosity does not change significantly within 8 hours, making it suitable for follow-up coating process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005093885110000011
    Figure BDA0005093885110000011
  • Figure BDA0005093885110000071
    Figure BDA0005093885110000071
  • Figure BDA0005093885110000072
    Figure BDA0005093885110000072
Patent Text Reader

Abstract

The invention relates to a method for inhibiting gelation of polyanion positive electrode material slurry, and belongs to the technical field of sodium ion batteries. The method comprises the following steps: S1, carrying out powder mixing on a polyanion positive electrode material and a first conductive agent to obtain mixed powder; adding the conductive slurry into the polyvinylidene fluoride glue solution, and stirring and mixing to obtain a mixed glue solution A; adding a non-fluorine binder into N-methyl pyrrolidone, and stirring and mixing to obtain a mixed glue solution B; s2, adding 1 / 2-2 / 3 of the mixed powder into the mixed glue solution A, and performing staged stirring to obtain mixed slurry A; adding the residual mixed powder into the mixed glue solution B, and performing staged stirring to obtain mixed slurry B; and S3, stirring and mixing the mixed slurry A and the mixed slurry B to obtain the polyanion positive electrode material slurry. According to the method, gelation of the slurry is effectively slowed down, and the coating window period of the slurry is prolonged, so that the coating quality of the polyanion positive plate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for inhibiting the gelation of polyanion positive electrode material slurry. Background Art

[0002] Sodium-ion batteries have attracted much attention due to their cost-effectiveness and abundance of raw materials. Their working principle is similar to that of lithium-ion batteries, using the reversible insertion and removal of sodium ions between the positive and negative electrodes to achieve energy storage and release. Sodium-ion batteries have broad application prospects in low-speed electric vehicles and energy storage. As the key to the performance of sodium-ion batteries, the processing performance of polyanion positive electrode materials is crucial. Since the binder of the polyanion positive electrode material commonly used in the industry is polyvinylidene fluoride, although it has good electrochemical properties, bonding strength and stability, polyvinylidene fluoride is prone to elimination reactions due to its poor alkali resistance. After removing hydrogen fluoride and water, the double bonds generated are prone to cross-linking reactions to form a gel. The elimination reaction principle is as follows:

[0003]

[0004] In addition, the molecular chain regularity of polyvinylidene fluoride homopolymer is relatively high, and it is easy to cause continuous chain reactions, which may cause the slurry to gel at a faster rate, and once the slurry is gelled, it is difficult to return to its normal state.

[0005] In the preparation process of polyanion positive electrode materials, in order to ensure that the capacity of the material is close to the theoretical capacity, an excessive amount of sodium source is often used. However, excessive sodium content will lead to a high residual alkali content in the material, which will cause the battery slurry to gel easily and the battery to produce gas during charging and discharging. Invention patents CN117638039A and CN114497521A mention the addition of anti-gel acid to neutralize the residual alkali of the positive electrode material, but this method is not suitable for polyanion positive electrode materials, because the anion groups of polyanions are generally phosphate, pyrophosphate, sulfate, etc. When anti-acid gel is directly added, a large number of hydrogen ions of the acidic substance will enter the lattice of the positive electrode material and react with the anion group, thereby destroying the structural stability of the material. Therefore, the residual alkali neutralization of polyanion positive electrode materials must adopt a multi-step reaction, slow release, and more "gentle" method.

[0006] Based on the above background, it is still necessary to develop a method to inhibit the gelation of polyanion cathode material slurry. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a method for inhibiting the gelation of polyanion positive electrode material slurry. The polyanion positive electrode slurry prepared by this method can effectively slow down the occurrence of slurry gelation and extend the coating window period of the slurry, thereby improving the coating quality of the polyanion positive electrode sheet and improving the problem that the slurry cannot be coated after gelation or the coating yield is low.

[0008] The object of the present invention is to provide a method for inhibiting the gelation of a polyanion positive electrode material slurry, comprising the following steps:

[0009] S1, mixing the polyanion positive electrode material and the first conductive agent into powder to obtain a mixed powder;

[0010] Adding a conductive slurry to the polyvinylidene fluoride glue, stirring and mixing at 2000 rpm-3000 rpm for 60 min-90 min to obtain a mixed glue A; the polyvinylidene fluoride glue comprises polyvinylidene fluoride and N-methylpyrrolidone, and the conductive slurry comprises a second conductive agent and N-methylpyrrolidone;

[0011] Add a non-fluorine binder to N-methylpyrrolidone, and stir and mix at 2000 rpm-3000 rpm for 30 min-60 min to obtain a mixed adhesive solution B; the non-fluorine binder is selected from a polyacrylonitrile binder and / or a nitrile rubber binder;

[0012] S2, adding 1 / 2-2 / 3 of the mixed powder to the mixed glue A described in S1, stirring in stages to obtain a mixed slurry A;

[0013] Add the remaining mixed powder to the mixed glue solution B described in S1, and stir in stages to obtain a mixed slurry B;

[0014] S3, stirring and mixing the mixed slurry A and the mixed slurry B described in S2 to obtain a polyanion positive electrode material slurry.

[0015] In one embodiment of the present invention, in S1, the chemical formula of the polyanion positive electrode material is Na x M y N z ; wherein, M is selected from one or more of Mn, Fe and V, N is selected from phosphate and / or pyrophosphate, 1≤x≤4, 1≤y≤3, 1≤z≤4.

[0016] In one embodiment of the present invention, in S1, the first conductive agent is selected from one or more of conductive carbon black, acetylene black, Ketjen black, graphite, carbon nanotubes and carbon fibers; the second conductive agent is selected from one or more of carbon nanotubes, graphene and graphene oxide.

[0017] In one embodiment of the present invention, in S1, the mass ratio of the polyanion positive electrode material to the first conductive agent is (90-98):(0.5-5).

[0018] In one embodiment of the present invention, in S1, the mass fraction of the polyvinylidene fluoride glue is 5%-8%; the mass fraction of the conductive slurry is 0.8%-1%.

[0019] In one embodiment of the present invention, in S1, the mass fraction of the non-fluorine binder in the mixed glue B is 1%-3%.

[0020] In one embodiment of the present invention, in S1, the preparation of the mixed powder can make the conductive agent evenly coated on the surface of the positive electrode material, thereby improving the dispersibility of the mixed powder.

[0021] In one embodiment of the present invention, in S1, the feeding of the mixed slurry B cannot be reversed, otherwise it may cause uneven dispersion of the non-fluorine binder.

[0022] In one embodiment of the present invention, in S2, the two staged stirrings each include two stages, the first stage is stirring at a main speed of 15rpm-20rpm and a dispersion speed of 200rpm-500rpm for 10min-15min; the second stage is stirring at a main speed of 30rpm-50rpm and a dispersion speed of 1000rpm-1500rpm for 20min-30min.

[0023] In one embodiment of the present invention, in S3, the stirring is performed at 2000 rpm-3000 rpm for 90 min-120 min.

[0024] In one embodiment of the present invention, the mass ratio of the polyanion positive electrode material, polyvinylidene fluoride, the second conductive agent, and the non-fluorine binder in the polyanion positive electrode material slurry is (90-98):(0.5-2):(0.5-1.5):(0.5-2).

[0025] In one embodiment of the present invention, the mass ratio of the polyvinylidene fluoride to the non-fluorine binder is (0.5-2):1.

[0026] The technical solution of the present invention has the following advantages over the prior art:

[0027] (1) The method of the present invention uses polyvinylidene fluoride and non-fluorine binder for compounding, wherein the non-fluorine binder is added, and the non-fluorine binder can absorb the hydroxide ions (OH) released when polyvinylidene fluoride undergoes an elimination reaction when it encounters an alkali. -), and can also participate in the reaction with the water molecules formed by OH-, promoting the proton transfer reaction, that is, the intermediate formed after the proton transfer will undergo ring opening and rearrangement, resulting in the breakage of the triple bond of the cyano group to form a carbonyl group (C=O), and finally react to form a carboxylic acid. Carboxylic acid is a class of organic compounds containing a carboxyl group (-COOH), with a pH value of 3-5, which is weakly acidic, just enough to neutralize the strong alkalinity of the positive electrode slurry (the pH value of the aqueous solution of the polyanion positive electrode material is 9, and the pH value of the slurry is 12, which is strongly alkaline), which can effectively reduce the damage of the strong alkali to polyvinylidene fluoride. As the slurry gradually disperses evenly and the pH value tends to stabilize, that is, after the elimination reaction of polyvinylidene fluoride and the proton transfer reaction of the non-fluorine binder are basically complete, the slurry state can be stable, which is manifested by the inhibition of the gelation phenomenon of the polyanion positive electrode material.

[0028] (2) The method described in the present invention is to compound polyvinylidene fluoride and a non-fluorine binder, which, on the one hand, reduces the overall amount of polyvinylidene fluoride used and greatly reduces the possibility of cross-linking of polyvinylidene fluoride; on the other hand, the cyano group (-C≡N) in the non-fluorine binder has a strong polarity and exhibits good resistance to heat and chemical media, and can resist the chain reaction after the cross-linking of polyvinylidene fluoride.

[0029] (3) The method described in the present invention first adds part of the mixed powder to the mixed glue A to prepare mixed slurry A. Because the mixed powder contains residual alkali, the amount of the mixed powder is not large enough to cause a partial reduction reaction of the polyvinylidene fluoride. Then the remaining mixed powder is added to the mixed glue B to prepare a mixed slurry B. In addition to neutralizing the residual alkali in the mixed powder, the non-fluorine binder in the mixed glue B also has a portion of the residue to neutralize the polyvinylidene fluoride in the mixed slurry A that has undergone a partial reduction reaction to generate hydroxide ions. Through this step-by-step mixing method, the residual alkali in the mixed powder is slowly released, and the mixing uniformity of the active substance slurry is improved. The mixed slurry A and the mixed slurry B are then mixed, and the hydrogen ions in the non-fluorine binder further neutralize the hydroxide ions generated by the reduction reaction to maintain a good dispersion state of the slurry.

[0030] (4) The method of the present invention first prepares mixed slurry A and mixed slurry B respectively, and then stirs and mixes them to prepare polyanion positive electrode material slurry. On the one hand, the mixed powder can be fully infiltrated to improve the dispersibility of the slurry; on the other hand, the OH in the mixed glue A can be - ions, H in mixed gel B + The ions are fully released, so that the two can be neutralized during subsequent mixing, preventing the formation of gel later.

[0031] (5) The method described in the present invention improves the dispersibility of the slurry of the polyanion positive electrode material by optimizing the process steps and adjusting the stirring, and at the same time, exerts a holding force on the polyanion positive electrode material slurry with the help of the very small amount of dispersant components contained in the conductive slurry and the non-fluorine binder, thereby improving the stability of the polyanion positive electrode material slurry itself, inhibiting gelation, and maintaining the viscosity of the polyanion positive electrode material slurry without obvious changes within 8 hours, which is conducive to the smooth progress of the subsequent coating process. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.

[0033] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.

[0034] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.

[0035] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.

[0036] In the present invention, unless otherwise specified, the polyvinylidene fluoride glue used in the embodiments of the present invention is purchased from Arkema with a brand of HSV900, the solvent is N-methylpyrrolidone, and the mass fraction of polyvinylidene fluoride is 5%.

[0037] In the present invention, unless otherwise specified, the carbon nanotube slurry used in the embodiments of the present invention is purchased from Tiannai, with a brand name of LB36, the solvent is N-methylpyrrolidone, and the mass fraction of carbon nanotubes is 0.9%.

[0038] In the present invention, unless otherwise specified, the nitrile rubber used in the embodiments of the present invention is purchased from Putailai with a brand name of R05.

[0039] In the present invention, unless otherwise specified, the polyacrylonitrile used in the embodiments of the present invention is purchased from Putailai with the brand name LA31.

[0040] Example 1

[0041] The method for inhibiting the gelation of polyanion positive electrode material slurry of the present invention specifically comprises the following steps:

[0042] S1, sodium iron pyrophosphate and conductive carbon black are premixed in a vacuum state for 30 minutes to obtain a mixed powder;

[0043] Adding carbon nanotube slurry to polyvinylidene fluoride glue solution, stirring and mixing at 2500 rpm for 60 minutes under vacuum state to obtain mixed glue solution A;

[0044] Adding nitrile rubber to N-methylpyrrolidone, stirring and mixing at 2500 rpm for 60 minutes under vacuum, to obtain a mixed rubber solution B with a mass fraction of nitrile rubber of 3%;

[0045] S2, add 1 / 2 of the mixed powder to the mixed glue A, stir at a main speed of 15 rpm and a dispersion speed of 500 rpm for 15 minutes, and then turn the bottom over; then stir at a main speed of 30 rpm and a dispersion speed of 1500 rpm for 30 minutes, and then turn the bottom over again to obtain a mixed slurry A;

[0046] Add the remaining mixed powder to the mixed glue solution B, stir for 15 minutes at a main speed of 15 rpm and a dispersion speed of 500 rpm, and then turn the bottom over; then stir for 30 minutes at a main speed of 30 rpm and a dispersion speed of 1500 rpm, and then turn the bottom over again to obtain a mixed slurry B;

[0047] S3. Stir the mixed slurry A and the mixed slurry B at 2800 rpm for 120 min under vacuum to obtain a polyanion positive electrode material slurry with a solid content of 56%; wherein the mass ratio of sodium ferric pyrophosphate, conductive carbon black, polyvinylidene fluoride, carbon nanotubes, and nitrile rubber is 94:2:2:1:1.

[0048] The static viscosity (mPa·s) and dynamic viscosity (mPa·s) values ​​of the polyanion cathode material slurry within 16 hours were monitored by a rotational viscometer NDJ-1. The parameter conditions and results are shown in Table 1:

[0049] Table 1

[0050]

[0051] Example 2

[0052] Basically the same as Example 1, except for the solid content and ratio of the polyanion positive electrode material slurry: the solid content of the polyanion positive electrode material slurry is 58%; the mass ratio of sodium ferric pyrophosphate, conductive carbon black, polyvinylidene fluoride, carbon nanotubes, and nitrile rubber is 94.5:2:1:1:1.5.

[0053] The static viscosity (mPa·s) and dynamic viscosity (mPa·s) values ​​of the polyanion cathode material slurry within 16 hours were monitored by a rotational viscometer NDJ-1. The parameter conditions and results are shown in Table 2:

[0054] Table 2

[0055]

[0056] Example 3

[0057] Basically the same as Example 1, except for the solid content and ratio of the polyanion positive electrode material slurry: the solid content of the polyanion positive electrode material slurry is 54%; the mass ratio of sodium ferric pyrophosphate, conductive carbon black, polyvinylidene fluoride, carbon nanotubes, and nitrile rubber is 94:1.5:1.5:1:2.

[0058] The static viscosity (mPa·s) and dynamic viscosity (mPa·s) values ​​of the polyanion cathode material slurry within 16 hours were monitored by a rotational viscometer NDJ-1. The parameter conditions and results are shown in Table 3:

[0059] Table 3

[0060]

[0061] Example 4

[0062] The method is basically the same as Example 1, except that the non-fluorine binder nitrile rubber is replaced by polyacrylonitrile.

[0063] The static viscosity (mPa·s) and dynamic viscosity (mPa·s) values ​​of the polyanion cathode material slurry within 16 hours were monitored by a rotational viscometer NDJ-1. The parameter conditions and results are shown in Table 4:

[0064] Table 4

[0065]

[0066] Comparative Example 1

[0067] The method is basically the same as Example 1, except that the adding method of the nitrile rubber is different, and specifically comprises the following steps:

[0068] S1, sodium iron pyrophosphate and conductive carbon black are premixed in a vacuum state for 30 minutes to obtain a mixed powder;

[0069] Adding carbon nanotube slurry to polyvinylidene fluoride glue, stirring and mixing at 2500 rpm for 60 minutes under vacuum, and then adding nitrile rubber, stirring and mixing at 2500 rpm for 60 minutes under vacuum, to obtain mixed glue A;

[0070] S2, add 1 / 2 of the mixed powder to the mixed glue A, stir at a main speed of 15 rpm and a dispersion speed of 500 rpm for 15 minutes, and then turn the bottom over; then stir at a main speed of 30 rpm and a dispersion speed of 1500 rpm for 30 minutes, and then turn the bottom over again to obtain a mixed slurry A;

[0071] Add the remaining mixed powder to the mixed slurry A, stir for 15 minutes at a main speed of 15 rpm and a dispersion speed of 500 rpm, and then turn the bottom over; then stir for 30 minutes at a main speed of 30 rpm and a dispersion speed of 1500 rpm, and then turn the bottom over again to obtain a mixed slurry B;

[0072] S3. Stir the mixed slurry B at 2800 rpm for 120 min under vacuum to obtain a polyanion positive electrode material slurry with a solid content of 56%; wherein the mass ratio of sodium iron pyrophosphate, conductive carbon black, polyvinylidene fluoride, carbon nanotubes, and nitrile rubber is 94:2:2:1:1.

[0073] The static viscosity (mPa·s) and dynamic viscosity (mPa·s) values ​​of the polyanion cathode material slurry within 16 hours were monitored by a rotational viscometer NDJ-1. The parameter conditions and results are shown in Table 5:

[0074] Table 5

[0075]

[0076] Comparative Example 2

[0077] The method is basically the same as Example 1, except that the nitrile rubber is added in a different manner, and specifically comprises the following steps:

[0078] S1, sodium iron pyrophosphate and conductive carbon black are premixed in a vacuum state for 30 minutes to obtain a mixed powder;

[0079] Adding carbon nanotube slurry to polyvinylidene fluoride glue solution, stirring and mixing at 2500 rpm for 60 minutes under vacuum state to obtain mixed glue solution A;

[0080] S2, add 1 / 2 of the mixed powder to the mixed glue A, stir at a main speed of 15 rpm and a dispersion speed of 500 rpm for 15 minutes, and then turn the bottom over; then stir at a main speed of 30 rpm and a dispersion speed of 1500 rpm for 30 minutes, and then turn the bottom over again to obtain a mixed slurry A;

[0081] Add the remaining mixed powder and nitrile rubber to the mixed slurry A, stir at a main speed of 15 rpm and a dispersion speed of 500 rpm for 15 minutes, and then turn the bottom over; then stir at a main speed of 30 rpm and a dispersion speed of 1500 rpm for 30 minutes, and then turn the bottom over again to obtain a mixed slurry B;

[0082] S3. Stir the mixed slurry B at 2800 rpm for 120 min under vacuum to obtain a polyanion positive electrode material slurry with a solid content of 56%; wherein the mass ratio of sodium iron pyrophosphate, conductive carbon black, polyvinylidene fluoride, carbon nanotubes, and nitrile rubber is 94:2:2:1:1.

[0083] The static viscosity (mPa·s) and dynamic viscosity (mPa·s) values ​​of the polyanion cathode material slurry within 16 hours were monitored by a rotational viscometer NDJ-1. The parameter conditions and results are shown in Table 6:

[0084] Table 6

[0085]

[0086] Comparative Example 3

[0087] The method is basically the same as Example 1, except that the adding method of the nitrile rubber is different, and specifically comprises the following steps:

[0088] S1, sodium iron pyrophosphate and conductive carbon black are premixed in a vacuum state for 30 minutes to obtain a mixed powder;

[0089] Adding carbon nanotube slurry to polyvinylidene fluoride glue solution, stirring and mixing at 2500 rpm for 60 minutes under vacuum state to obtain mixed glue solution A;

[0090] S2, add 1 / 2 of the mixed powder to the mixed glue A, stir at a main speed of 15 rpm and a dispersion speed of 500 rpm for 15 minutes, and then turn the bottom over; then stir at a main speed of 30 rpm and a dispersion speed of 1500 rpm for 30 minutes, and then turn the bottom over again to obtain a mixed slurry A;

[0091] Add the remaining mixed powder to the mixed slurry A, stir for 15 minutes at a main speed of 15 rpm and a dispersion speed of 500 rpm, and then turn the bottom over; then stir for 30 minutes at a main speed of 30 rpm and a dispersion speed of 1500 rpm, and then turn the bottom over again to obtain a mixed slurry B;

[0092] S3. Add nitrile rubber to the mixed glue solution B, stir at 2800 rpm for 120 min under vacuum to obtain a polyanion positive electrode material slurry with a solid content of 56%; wherein the mass ratio of sodium ferric pyrophosphate, conductive carbon black, polyvinylidene fluoride, carbon nanotubes, and nitrile rubber is 94:2:2:1:1.

[0093] The static viscosity (mPa·s) and dynamic viscosity (mPa·s) values ​​of the polyanion cathode material slurry within 16 hours were monitored by a rotational viscometer NDJ-1. The parameter conditions and results are shown in Table 7:

[0094] Table 7

[0095]

[0096] Comparative Example 4

[0097] The method is basically the same as Example 1, except that the non-fluorine binder nitrile rubber is not added.

[0098] The static viscosity (mPa·s) and dynamic viscosity (mPa·s) values ​​of the polyanion cathode material slurry within 16 hours were monitored by a rotational viscometer NDJ-1. The parameter conditions and results are shown in Table 8:

[0099] Table 8

[0100]

[0101]

[0102] It can be seen from Tables 1 to 8 that by adding the non-fluorine binder using the method of the embodiment, the polyanion positive electrode material slurry can basically remain stable for 8 hours, and the static viscosity is less than 15000 MPa·s after 8 hours, which can well meet the needs of slurry coating; however, when the addition method of the non-fluorine binder is changed or the non-fluorine binder is not added, the static viscosity of the slurry is greater than 17000 MPa·s after 3 hours, and the slurry gels, resulting in uneven dispersion of the binder and the active powder, which is not conducive to the subsequent coating process.

[0103] Comparative Example 1: Non-fluorine binder (nitrile rubber) and carbon nanotube slurry are directly added to polyvinylidene fluoride glue, stirred and then added to the mixed powder in two steps. However, the mixed powder cannot convert hydroxide ions (OH - ) are all released, so that the pH value of the slurry remains stable. Therefore, its static viscosity increases significantly after 3 hours. The rate of increase of dynamic viscosity is slower than that of static viscosity. This shows that during the continuous stirring process, the hydroxide ions (OH - ) is slowly released and reacts with the non-fluorine binder, which slows down the gelation time of the slurry to a certain extent.

[0104] Comparative Example 2 is to add non-fluorine binder at the same time as the second addition of powder, and the effect is the same as that of Comparative Example 1. Also at 3h, the viscosity has increased significantly.

[0105] In comparative example 3, the non-fluorine binder is added after the powder is added. Since the materials have been mixed, the hydroxide ions are partially released, so the gel time is delayed to 4 hours. This also illustrates the importance of step-by-step material mixing from another perspective. First, it can ensure that the mixed powder can be fully infiltrated with the binder (including the non-fluorine binder and the polyvinylidene fluoride glue) to improve the dispersibility of the slurry. Second, it can ensure that the OH in the mixed glue A - ions, H in mixed gel B + The ions are fully released, so that the two can be neutralized during subsequent mixing, preventing the formation of gel later.

[0106] In comparative example 4, no non-fluorine binder is added, and it can be seen that the slurry stability time is less than 1 hour. This shows that even if the step-by-step mixing method is adopted, but no non-fluorine binder is added, the stability of the slurry can only be maintained for one hour.

[0107] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for inhibiting the gelation of a polyanion positive electrode material slurry, characterized in that: The following steps are involved: S1, mixing the polyanion positive electrode material and the first conductive agent into powder to obtain a mixed powder; Adding a conductive slurry to the polyvinylidene fluoride glue, stirring and mixing at 2000 rpm-3000 rpm for 60 min-90 min to obtain a mixed glue A; the polyvinylidene fluoride glue comprises polyvinylidene fluoride and N-methylpyrrolidone, and the conductive slurry comprises a second conductive agent and N-methylpyrrolidone; Add a non-fluorine binder to N-methylpyrrolidone, and stir and mix at 2000 rpm-3000 rpm for 30 min-60 min to obtain a mixed adhesive solution B; the non-fluorine binder is selected from a polyacrylonitrile binder and / or a nitrile rubber binder; S2, adding 1 / 2-2 / 3 of the mixed powder to the mixed glue A described in S1, stirring in stages to obtain a mixed slurry A; Add the remaining mixed powder to the mixed glue solution B described in S1, and stir in stages to obtain a mixed slurry B; S3, stirring and mixing the mixed slurry A and the mixed slurry B described in S2 to obtain a polyanion positive electrode material slurry.

2. The method for inhibiting gelation of polyanion positive electrode material slurry according to claim 1, characterized in that: In S1, the chemical formula of the polyanion cathode material is Na x M y N z ; wherein, M is selected from one or more of Mn, Fe and V, N is selected from phosphate and / or pyrophosphate, 1≤x≤4, 1≤y≤3, 1≤z≤4.

3. The method for inhibiting gelation of polyanion positive electrode material slurry according to claim 1, characterized in that: In S1, the first conductive agent is selected from one or more of conductive carbon black, acetylene black, Ketjen black, graphite, carbon nanotubes and carbon fibers; the second conductive agent is selected from one or more of carbon nanotubes, graphene and graphene oxide.

4. The method for inhibiting gelation of polyanion positive electrode material slurry according to claim 1, characterized in that: In S1, the mass ratio of the polyanion positive electrode material to the first conductive agent is (90-98):(0.5-5).

5. The method for inhibiting gelation of polyanion positive electrode material slurry according to claim 1, characterized in that: In S1, the mass fraction of the polyvinylidene fluoride glue is 5%-8%; the mass fraction of the conductive slurry is 0.8%-1%.

6. The method for inhibiting gelation of polyanion positive electrode material slurry according to claim 1, characterized in that: In S1, the mass fraction of the non-fluorine binder in the mixed glue solution B is 1%-3%.

7. The method for inhibiting gelation of polyanion positive electrode material slurry according to claim 1, characterized in that: In S2, the two staged stirrings each include two stages. The first stage is stirring at a main speed of 15rpm-20rpm and a dispersion speed of 200rpm-500rpm for 10min-15min; the second stage is stirring at a main speed of 30rpm-50rpm and a dispersion speed of 1000rpm-1500rpm for 20min-30min.

8. The method for inhibiting gelation of polyanion positive electrode material slurry according to claim 1, characterized in that: In S3, the stirring is performed at 2000 rpm to 3000 rpm for 90 min to 120 min.

9. The method for inhibiting gelation of polyanion positive electrode material slurry according to claim 1, characterized in that: The mass ratio of the polyanion positive electrode material, polyvinylidene fluoride, the second conductive agent and the non-fluorine binder in the polyanion positive electrode material slurry is (90-98):(0.5-2):(0.5-1.5):(0.5-2).

10. The method for inhibiting gelation of polyanion positive electrode material slurry according to claim 9, characterized in that: The mass ratio of the polyvinylidene fluoride to the non-fluorine binder is (0.5-2):1.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode slurry and preparation method thereof

    CN114497521A

  • Sodium-ion battery positive electrode slurry for improving gel, preparation method of pole piece and pole piece

    CN117638039A